A novel histone deacetylase 6 inhibitor improves myelination of Schwann cells in a model of Charcot–Marie–Tooth disease type 1A. (27th September 2020) - Ha, Nina; Choi, Young Il; Jung, Namhee; Song, Ju Young; Bae, Dae Kwon; Kim, Min Cheol; Lee, Yong Jae; Song, Hyeseung; Kwak, Geon; Jeong, Soyeon; Park, Saeyoung; Nam, Soo Hyun; et al.
Abstract : Background and Purpose: Charcot–Marie–Tooth (CMT) disease is the most common hereditary peripheral neuropathy. CMT type 1A (CMT1A) accounts for approximately 50% of CMT patients and is linked to PMP22 gene duplication. Histone deacetylase‐6 (HDAC6) has pleiotropic effects, such as regulating lipid homeostasis and cellular stress. Although HDAC6 has been regarded as a promising drug target for neurodegenerative diseases, its inhibition has not yet been tested in CMT1A. Here we have tested the therapeutic potential of CKD‐504, a clinical stage HDAC6 inhibitor, in a mouse model of CMT1A Experimental Approach: The potency and selectivity of CKD‐504 was evaluated, using a HDAC enzyme panel assay and western blots. The therapeutic potential of CKD‐504 was evaluated using behavioural testing and electrophysiological assessments in the C22 mouse model of CMT1A. PMP22 protein expression and aggregation were analysed in mesenchymal stem cell‐derived Schwann cells from CMT1A patients and sciatic nerves from C22 mice. Key Results: The HDAC6 inhibitor, CKD‐504, modulated molecular chaperon proteins such as HSP90 and HSP70, which are involved in the folding/refolding of proteins such as PMP22. CKD‐504 treatment restored myelination in both mesenchymal stem cell‐derived Schwann cells from CMT1A patients and sciatic nerves of C22 mice and improved the axonal integrity of the sciatic nerve, leading to behavioural, electrophysiological, and histological improvements in C22 mice. Conclusion and Implications: A novel HDAC6 inhibitor, CKD‐504, has potent therapeutic efficacy for CMT1A.